Innovation and the International Firm Structure: Theory and Evidence from German Firm-Level Data - Thorsten Hansen (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
This paper studies the impact of innovation on the organizational structure. The theoretical framework predicts that a larger parental pool of knowledge raises the probability of offshoring. This holds in a national as well as an international context. However, when the producer loses territorial protection, the changeover from non-integration to integration is delayed. Employing data on German firms investing in Eastern Europe finds empirical evidence for the theoretical predictions. The results are robust to different measurements and an instrumental variable regression.
urn:nbn:de:bvb:19-epub-13239-0
Keywords: D23; D51; F23; L14; L21; L22; L23; 330; Innovation; Multinationales Unternehmen; Organisationsstruktur; Auslandsverlagerung; Patentrecht; Unternehmenszentrale; Ausländische Tochtergesellschaft; Theorie; Schätzung; Deutschland; Osteuropa